2011
DOI: 10.1002/mus.22018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fatigue on knee position sense is not dependent upon the muscle group fatigued

Abstract: Muscle fatigue affects knee position sense, and the deleterious effect is not different depending upon the muscle group fatigued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…This hinders provision of immediate feedback for athletes and coaches during field evaluation and slows the planning of training or rehabilitation sessions. 1,4,5 Based on the aforementioned arguments, the inclinometer is an affordable and portable instrument that provides a valid and reliable method, applicable in training sessions and even in competition, when exertion may lead to an injury event. Studies that evaluated the effects of fatigue on proprioception 6 reported impairments in the acuity of athletes during knee JPS tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hinders provision of immediate feedback for athletes and coaches during field evaluation and slows the planning of training or rehabilitation sessions. 1,4,5 Based on the aforementioned arguments, the inclinometer is an affordable and portable instrument that provides a valid and reliable method, applicable in training sessions and even in competition, when exertion may lead to an injury event. Studies that evaluated the effects of fatigue on proprioception 6 reported impairments in the acuity of athletes during knee JPS tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This target position was 50° of knee flexion in the dominant leg, which refers to the intermediate range of knee flexion, where mediation by muscle sensors in the detection of knee position predominates. 5 After 5 seconds, they were asked to return to the initial position (full knee extension). At a spoken "reposition" order, the subjects tried to reproduce the target joint angle as accurately as possible and maintain the estimated position for 3 seconds until a "return" order was given.…”
Section: Jsr Technical Reports 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue is defined as an exercise-induced reduction in the ability of a muscle to generate force or power due to peripheral and/or central factors, related with an increase in perceived exertion, which can be defined as the intensity of subjective effort, strain, discomfort or fatigue sensation that one feels during exercise (Gandevia, 2001). The effects of exercise-induced muscle fatigue on joint proprioception have been extensively investigated in the last decades (Allen & Proske, 2006;Brockett, et al, 1997;Carpenter, et al, 1998;Forestier & Bonnetblanc, 2006;Forestier, Teasdale, & Nougier, 2002;Givoni, Pham, Allen, & Proske, 2007;Ju, Wang, & Cheng, 2010;Lattanzio, Petrella, Sproule, & Fowler, 1997;Lee, Liau, Cheng, Tan, & Shih, 2003;Miura, et al, 2004;Myers, Guskiewicz, Schneider, & Prentice, 1999;Paschalis, et al, 2008;Paschalis, et al, 2007;Ribeiro, Santos, Gonçalves, & Oliveira, 2008;Ribeiro, Venâncio, Quintas, & Oliveira, 2011;Saxton, et al, 1995;Skinner, et al, 1986;Torres, et al, 2010;Tripp, et al, 2004;Vila-Cha, et al, 2011;Walsh, Hesse, Morgan, & Proske, 2004) (Table 4). The majority of studies investigating the effects of exercise-induced fatigue on proprioception have been conducted in the knee joint.…”
Section: Exercise-induced Muscle Fatiguementioning
confidence: 99%
“…It is the basic element of the spontaneous control of movement, balance and joint stability. Therefore, it is necessary for the execution of walking and daily and sport activities 3 .…”
Section: Introductionmentioning
confidence: 99%